Answer:
3x - 4 and 2x + 15.
Explanation:
6x^2 + 37x - 60.
We can use the 'ac' method to factor this. The a and c refer to the coefficients a and c in the general quadratic ax^2 + bx + c.
Here ac = 6*-60 = -360.
Now we want 2 numbers whose sum = the 'b' coefficient ( that is 37) and whose product is -360.
We can then split up the 37x into 2 terms.
-360 = -2*2*2*3*3*5
The numbers we require are 3*3*5 and - 2*2*2 = 45 and -8 which sum to + 37, so we can rewrite the original expression as:
6x^2 + 45x - 8x - 60
= 3x(2x + 15) - 4(2x + 15)
= (3x - 4)(2x + 15) (answer).